Evolving response to smart irrigation controllers in high water‐use central Florida homes. Issue 1 (19th November 2018) - Morera, Maria C.; Monaghan, Paul F.; Dukes, Michael D.
Abstract : Efforts to improve urban irrigation efficiency through the promotion of smart controllers represent a critical water resource management strategy in Florida. However, targeted initiatives require knowledge of household characteristics and preferences among high irrigators to ensure acceptance and continued use of the devices. This article compares survey data collected in 2014 and 2017 from high‐water‐use homes in Orange County, Florida, with soil moisture sensor and evapotranspiration controllers installed, to evaluate long‐term response to the technologies. Results indicate the perceived water‐saving effectiveness of the controllers and whether challenges were experienced operating them significantly predicted satisfaction with the controllers and the likelihood of continuing to use them, respectively, during both periods. The likelihood of continued use after 2017 was almost 12 times higher if a respondent was satisfied with the controller and 82% lower if any challenge was experienced with it. Increased familiarity and comfort with the controllers would enhance long‐term adoption.